HUBUNGAN KETINGGIAN BLOK DENGAN HEMODINAMIK INTRA SPINAL ANESTESI DI RUMAH SAKIT MUHAMMADIYAH YOGYAKARTA - Arfin Kurniadita; Jenita Doli Tine Donsu; Induniasih Induniasih (Poltekkes Kemenkes Yogyakarta, 2021)
Background: Regional anesthetics Sub Arachnoid Block (SAB) produces a certain block height which causes hemodynamic instability. This happens because vasodilation of blood vessels and sympathetic nerves are blocked so that it dominates the performance of the parasympathetic nerves. Objective: To determine the relationship of block height with intra-spinal hemodynamic anesthesia at surgery room in PKU Muhammadiyah Yogyakarta Hospital Research Methods: This research is a non-experimental quantitative research with analytic correlational research design and cross sectional survey research design. The study sample consisted of 50 respondents spinal anesthesia patients. sampling with consecutive sampling, the statistical test used is the chi square test. Research Results: The height of the spinal anesthesia respondent block majority of respondents experienced surgery and skin block height (block under Thoracalis 7). The majority of intra-spinal anesthesia hemodynamic respondents had stable blood pressure, pulse, and MAP. There is a significant relationship between block height (surgery, skin / block under thoracalis 7 and high spinal block / above thoracalis 6) with intra-spinal anesthesia blood pressure. There is a significant relationship between the height of the block height block (surgery, skin / block below thoracalis 7 and high spinal block / above thoracalis 6) with intra-spinal anesthesia pulse. There is a significant relationship between the height of the block height block (surgery, skin / block below thoracalis 7 and high spinal block / above thoracalis 6) with intra spinal anesthesia MAP. Conclusion: There is a corelations between the height of the block with hemodynamic intra spinal anesthesia in the IBS RS PKU Muhammadiyah Yogyakarta..